Additive Manufacturing of Zirconia Ceramic and Its Application in Clinical Dentistry: A Review - Leila Nasiry Khanlar; Alma Salazar Rios; Ali Tahmaseb; Amirali Zandinejad (MDPI AG, 2021)
Additive manufacturing (AM) has many advantages and became a valid manufacturing technique for polymers and metals in dentistry. However, its application for dental ceramics is still in process. Among dental ceramics, zirconia is becoming popular and widely used in dentistry mainly due to its outstanding properties. Although subtractive technology or milling is the state of art for manufacturing zirconia restorations but still has shortcomings. Utilizing AM in fabricating ceramics restorations is a new topic for many researchers and companies across the globe and a good understanding of AM of zirconia is essential for dental professional. Therefore, the aim of this narrative review is to illustrate different AM technologies available for processing zirconia and discus their advantages and future potential. A comprehensive literature review was completed to summarize different AM technologies that are available to fabricate zirconia and their clinical application is reported. The results show a promising outcome for utilizing AM of zirconia in restorative, implant and regenerative dentistry. However further improvements and validation is necessary to approve its clinical application.